2018
DOI: 10.3390/met8080608
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Deformability of a Fe-Cr-Mn-Ni Austenite Stainless Steel with High Nitrogen and High Carbon Contents

Abstract: High temperature deformability and fracture behavior of deformation-processed high nitrogen high carbon Fe-Cr-Mn-Ni stainless steel rods were studied. The effective fracture elongation increased rapidly from 1000 °C, and reached high values (>45%) at 1100–1200 °C, accompanied by strain softening and stress serrations, supporting periodic dynamic recrystallization (DRX). Dynamically recrystallized grains were observed close to the fracture surface, suggesting that active DRX worked until its fracture. Pre-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…4. The higher oxygen content revealed by EDS spectra from crack initiation site suggests that the higher oxygen content due to the reduction of Fe 2 O 3 by Zr and dissolution of oxygen into matrix is responsible for the low deformability It is interesting to note that the strength increases with increasing fraction of scrap, which can be attributed to the increase of oxygen content [11], [12]. The ductility decreased slightly with increase of scrap fraction.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…4. The higher oxygen content revealed by EDS spectra from crack initiation site suggests that the higher oxygen content due to the reduction of Fe 2 O 3 by Zr and dissolution of oxygen into matrix is responsible for the low deformability It is interesting to note that the strength increases with increasing fraction of scrap, which can be attributed to the increase of oxygen content [11], [12]. The ductility decreased slightly with increase of scrap fraction.…”
Section: Resultsmentioning
confidence: 97%
“…Oxide contamination of scrap may increase the oxide content in newly cast alloy after remelting, which may deteriorate the properties. Some scrap cake was mixed with Fe 2 O 3 particle to investigate the possible inclusion of iron oxide from steel storage containers during storage and handling of scrap [11]. In order to investigate the possible effects of impurities introduced from the scrap, some model alloys without scrap addition were cast with the intentional addition Fe and Fe 2 O 3 to simulate and examine the most probable impurities of Fe and O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grain size including twin boundaries was measured to be 11.3 μm, 6.4 μm and 1.9 μm for three alloys, respectively. The decrease of grain size with increase of carbon content in (NiCo)75Cr17Fe8Cx MEAs is attributed to grain boundary pinning effect of carbide particles [25][26][27]. A higher dislocation storage and the lower recovery due to carbon atoms and carbides may have contributed to grain size refinement [27].…”
Section: Effect Of Carbon On the Microstructural Evolutionmentioning
confidence: 99%
“…Klimova et al [25] found that the solubility of interstitial carbon in fcc solid solution increases with a decrease of Cr content. The decrease of Cr content from 20 at.% to 6.3 at.% was reported to increase the carbon solubility from 0.36 at.% to 1.61 at.% in CoCr x FeMnNi (x = 1, 0.25) at 1000 • C. Carbon atoms are also known to strengthen the steels [26] and HEAs [25,27,28] through solution strengthening, precipitation and/or grain-size strengthening. In this study, mechanical properties and microstructural evolution of non-equiatomic quaternary Alloy-600-type CoNiCrFe with and/or without carbon addition at room and cryogenic temperatures were studied.…”
Section: Introductionmentioning
confidence: 99%